2021
DOI: 10.5815/ijieeb.2021.01.01
|View full text |Cite
|
Sign up to set email alerts
|

PriceCop – Price Monitor and Prediction Using Linear Regression and LSVM-ABC Methods for E-commerce Platform

Abstract: In early 2020, the world was shocked by the outbreak of COVID-19. World Health Organization (WHO) urged people to stay indoors to avoid the risk of infection. Thus, more people started to shop online, significantly increasing the number of e-commerce users. After some time, users noticed that a few irresponsible online retailers misled customers by hiking product prices before and during the sale, then applying huge discounts. Unfortunately, the "discounted" prices were found to be similar or only slightly low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
(18 reference statements)
0
13
0
1
Order By: Relevance
“…В багатьох інформаційних експертних системах чи в інформаційних системах класифікації використовуються багатовимірні лінійні чи нелінійні регресії, коефіцієнти яких при змінних знаходяться методом найменших квадратів [1][2][3][4][5][6][7][8]. В роботах [9][10][11] була сформульована наступна проблема.…”
Section: вступunclassified
“…В багатьох інформаційних експертних системах чи в інформаційних системах класифікації використовуються багатовимірні лінійні чи нелінійні регресії, коефіцієнти яких при змінних знаходяться методом найменших квадратів [1][2][3][4][5][6][7][8]. В роботах [9][10][11] була сформульована наступна проблема.…”
Section: вступunclassified
“…e experimental results indicated that supplier's profit can be affected by many aspects and show different effects. Shahrel et al [21] designed a Web application called Price Cop to help customers monitor product pricing, which helps users plan before they buy. A price forecasting model is established by using linear regression technique.…”
Section: Related Workmentioning
confidence: 99%
“…The purpose of the paper, based on factor analysis [8], is to identify homogeneous groups of hybrid threats in the civil security sector, analyze the risk level of hybrid threats' spreading of related to crime; on the basis of correlation analysis [9] to determine the factors that shape the capabilities or vulnerabilities [10] to reduce the risk of illegal armed groups. Based on the linear regression [11] model, to assess the risk of the spread of the hybrid threat "activities of illegal armed groups", to identify priority factors of reduce this risk and to build an appropriate model and forecast.…”
Section: The Purpose Of the Papermentioning
confidence: 99%